2015
DOI: 10.1095/biolreprod.114.122770
|View full text |Cite
|
Sign up to set email alerts
|

Cumulus Cell-Expressed Type I Interferons Induce Cumulus Expansion in Mice1

Abstract: Ovulation resembles the inflammatory response. The purpose of the present study was to examine the expression and role of type I interferons (IFNs) Ifnalpha and Ifnbeta in mouse ovaries during the process of ovulation. An in vivo injection of equine chorionic gonadotropin (CG)-human CG (hCG) stimulated Ifnalpha and Ifnbeta mRNA in cumulus-oocyte complexes (COCs) within 6 h. Type I IFN receptor (Ifnar1 and Ifnar2) genes were also expressed in preovulatory follicles without a change by hCG. Immunofluorescent stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…In the in vitro COCs culture experiments, cumulus cell proliferation and expansion had important effects on oocyte maturation and quality, whereas PTX3, HAS2 and PTGS2 are important genes that affected cumulus cell proliferation [29, 30]. This study showed that miR-375 could regulate the expression levels of PTX3, HAS2 and PTGS2 through its target genes.…”
Section: Discussionmentioning
confidence: 96%
“…In the in vitro COCs culture experiments, cumulus cell proliferation and expansion had important effects on oocyte maturation and quality, whereas PTX3, HAS2 and PTGS2 are important genes that affected cumulus cell proliferation [29, 30]. This study showed that miR-375 could regulate the expression levels of PTX3, HAS2 and PTGS2 through its target genes.…”
Section: Discussionmentioning
confidence: 96%
“…The reduced expression of GJA1 in CCs after oocyte maturation is beneficial (Edry et al 2006) because it is related to cumulus expansion and decreased diffusion of cAMP and cGMP from the CCs to the oocyte, which is followed by the end of meiotic arrest and extrusion of the first polar body (Shao et al 2015). Conversely, PTGS2 is the key enzyme in prostaglandin E biosynthesis and is also involved in regulation of CC expansion during the ovulatory process in mice (Davis et al 1999;Jang et al 2015). In the present study, Ptgs2 mRNA transcripts were upregulated in CCs after oocyte maturation, as described previously for cattle (Nuttinck et al 2002), mice (Shao et al 2015) and humans (Feuerstein et al 2007;Wathlet et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Human and bovine granulosa cells express TLR1-9 (Zhou et al 2009, Price and Sheldon 2013. Similarly, murine cumulus cells express TLR2 and TLR4, and activation of these pattern recognition receptors induces events associated with ovulation such as cumulus expansion (Shimada et al 2006, Shimada et al 2008, Jang et al 2015. Furthermore, endocrine regulation of TLRs was evident in bovine and murine granulosa cells using FSH or EGF (Shimada et al 2006, Shimada et al 2008, Price and Sheldon 2013.…”
Section: Innate Immunity In the Ovarymentioning
confidence: 99%